1989
DOI: 10.1111/j.1365-2044.1989.tb09145.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of fibrescope‐guided nasotracheal intubation

Abstract: SummaryThe cardiovascular efects ojjibrescope-guided nasotracheal intubation were compared to those o f a control group of patients who w'ere intubated using the Macintosh laryngoscope. The 60 Stimulation of the upper respiratory tract by laryngoscopy and tracheal intubation induces sympathetically-mediated tachycardia and hypertension.',? This pressor response can cause significant morbidity and mortality, and may be hazardous particularly for patients with cerebral or cardiovascular disease.'." It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 18 publications
2
11
3
Order By: Relevance
“…2, respectively). Heart rate and MAP at baseline were significantly higher than values recorded at one, 3,5,10,15,20,25, and 30 minutes in Groups T and D (P b 0.01).…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…2, respectively). Heart rate and MAP at baseline were significantly higher than values recorded at one, 3,5,10,15,20,25, and 30 minutes in Groups T and D (P b 0.01).…”
Section: Resultscontrasting
confidence: 61%
“…The usual hemodynamic responses to laryngoscopy and intubation in an anesthetized patient are hypertension, tachycardia [4], and arrhythmia [5]. The cardiovascular response to tracheal intubation, although transient, may be harmful to some patients, mainly those with myocardial or cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was in contrast to study done by Sun et al [7], Smith et al [8] which showed no significant difference in blood pressure and heart rate between the two groups (p=0.13). This inter study difference may be related to their use of intravenous sedation prior to intubation which causes decrease in rise of mean arterial pressure and heart rate.…”
Section: Discussioncontrasting
confidence: 87%
“…The differences between our findings and those of Smith et al [5] may be due to differences in anaesthetic technique. Smith et al used vecuronium in the dose of 0.125 mg/kg.…”
Section: Discussioncontrasting
confidence: 56%